Effectiveness of DP3AP2KB Program Services (Women's Empowerment and Child Protection, Population Control and Family Planning Service) in Handling Violence Against Women and Children in Cimahi City - Nadila, Dini; Aswin, Aswin (Westscience Press, 2024)
In addition to providing services such as public complaints, victim outreach, case management, temporary shelter, mediation, and victim support, the Women's Empowerment and Child Protection Service, Population Control and Family Planning (DP3AP2KB) is a government service unit that offers these services. Children and women who have Cimahi ID cards (or who are domiciled in Cimahi and/or who have experienced gender-based violence and have a Crime Scene (TKP) in the Cimahi City area are eligible to receive free integrated services. This is the mission of the organization. In addition to providing services for victims of physical, psychological, and sexual violence, the organization also provides services for victims of trafficking, pornography, bullying, child labor, and children who are in conflict with the law. The use of violence is one of the acts that constitutes a significant violation of human rights. Specifically, this is due to the fact that acts of violence never reflect the standards and values that are associated with human rights. Consequently, in order to achieve a deterrent effect, those who commit acts of violence should be punished as soon as possible. On purpose, individuals or organizations engage in acts of violence with the intention of oppressing those who are vulnerable in order to ensure that they continue to endure suffering. Depending on the circumstances, this violence may take the form of either physical or psychological aggression. When it comes to acts of physical violence, such as someone hitting or kicking another person, and so on. On the other hand, psychological violence includes things like coercing other people to do things that they do not enjoy. There are impacts that can be harmful to the victim that are associated with both forms. a. physical violence; b. sexual violence; c. economic violence; d. social violence; e. psychological violence; f. domestic neglect; and g. exploitation are all examples of distinct types of violence. Ascertaining the efficacy of the DP3AP2KB Program Service in dealing with acts of violence against women and children, determining how the program can function without any hiccups, identifying the programs that are available, and determining the role that human resources play in the DP3AP2KB program in dealing with acts of violence against women and children were the objectives of this study. Within the scope of this investigation, a qualitative descriptive methodology was utilized. The research was conducted using a qualitative methodology and a descriptive research type technique. The informants needed in this study are the DP3AP2KB office, victims of domestic violence and the community or fostered families of Cimahi City.